Acute Necrotizing Pancreatitis Complicating Uteroplacental Apoplexy - Chong-U Cheang; Sai-Wai Ho; Yi-Torng Tee; Chi-Feng Su; Gin-Den Chen (Elsevier, 2007)
Objective: Abruptio placentae induced by acute pancreatitis during pregnancy is very rare. We present a pregnant woman with a series of complications due to acute necrotizing pancreatitis. Case Report: Presented herein is a 21-year-old, nulliparous woman at 33 weeks' gestation. The initial episode of abdominal pain was thought to be acute appendicitis (which in actuality was identified to be acute pancreatitis) and was complicated with abruptio placentae, uteroplacental apoplexy, and intrauterine fetal demise. Sterile necrotizing pancreatitis was confirmed by computerized axial tomography and total negativity of bacterial cultures taken from blood and ascites during the hospitalization. Nonsurgical management with conservative treatment was employed and the patient recovered gradually. Conclusion: Acute pancreatitis is difficult to diagnose during pregnancy. It presents as a systemic inflammatory response syndrome resulting in hemodynamic changes and may lead to abruptio placentae. Nonsurgical conservative treatment may be useful in such patients.